Kecerdasan Spiritual Dikembangkan Melalui Metode Bercerita Pada Anak - KROBO, ANDRIANUS (Jurnal Ilmu Pendidikan Indonesia, 2019)
The purpose of this study was to determine the development of spiritual intelligence through a method of telling stories to children in group B1 of YPPK TK Christ Terang Dunia. The results of the study showed that the spiritual intelligence of group B1 children in YPPK TK Christ Terang Dunia can be developed through storytelling methods.